Rare bird documentation form for Peregrine Falcon at Sandy Beach at Coralville Reservoir, 1981 - Newlon, Michael C.et al (1981)
Rare bird documentation form for a Peregrine Falcon at Sandy Beach at Coralville Reservoir in Johnson County, IA on April 26, 1981. Epson - sheet feed